Price Points and Price Rigidity - LEVY, Daniel (Institutional Knowledge at Singapore Management University, 2011)
We study the link between price points and price rigidity using two data sets: weekly scanner data and Internet data. We ﬁnd that ‘‘9’’ is the most frequent ending for the penny, dime, dollar, and ten-dollar digits; the most common price changes are those that keep the price endings at ‘‘9’’; 9-ending prices are less likely to change than non-9-ending prices; and the average size of price change is larger for 9-ending than non-9- ending prices. We conclude that 9-ending contributes to price rigidity from penny to dollar digits and across a wide range of product categories, retail formats, and retailers.